Differential Roles of GluN2B in Two Types of Chemical-induced Long Term Potentiation-mediated Phosphorylation Regulation of GluA1 at Serine 845 in Hippocampal Slices. (1st May 2020) - Zhang, Bin; Fang, Weiqing; Ma, Wu; Xue, Fusheng; Ai, Heng; Lu, Wen
Highlights: Forskolin and rolipram-induced cLTP regulates GluN2B pY1472 and GluA1 pS845 levels in hippocampus. Glycine-induced cLTP modulates GluA1 pS845 level but not GluN2B pY1472 level in hippocampus. Blockade of GluN2B hampers the increase in GluA1 pS845 level in forskolin and rolipram-induced cLTP. Blockade of GluN2B exerts minimal effects on GluA1 pS845 level in glycine-induced cLTP. Abstract: Synaptic plasticity, such as long term potentiation (LTP) and long term depression (LTD), underlies the cellular mechanism of learning and memory. Chemical-induced LTP (cLTP), which facilitates biochemical analysis of molecular changes in brain slices or neuronal cultures, has been accepted as an in vitro model to explore synaptic plasticity. cLTP, by either forskolin and rolipram (F&R) or glycine, is thought to be dependent on NMDA receptor. However, subunit-specific dependence and regulation of the NMDA receptor in cLTP remain poorly understood. In the present study, we found that phosphorylation level of GluN2B at tyrosine 1472 was modulated by F&R-induced LTP but not by glycine-induced LTP in hippocampal slices. Furthermore, an increased phosphorylation level of GluA1 at serine 845 by F&R-induced LTP rather than glycine-induced LTP was dependent on the activation of GluN2B, which is supported by the results from GluN2B antagonists, small interfering peptide and CRISPR-Cas9-mediated knock out of GluN2B. Taken together, we reveal the significant role of GluN2B in F&R-induced LTP, uncovering the role of GluN2B subunit of NMDA receptor in a specified cLTP.